Nano-imprinting glue with ultraviolet aging resistance and high refractive index and preparation method of nano-imprinting glue

By using inorganic composite nanoparticles of titanium oxide, photocurable resin monomer, UV absorber and antioxidant in nanoimprinting glue, the problem of material aging of diffraction light waveguides under ultraviolet light is solved, and high refractive power is achieved and resistance to UV aging.

CN119463711APending Publication Date: 2025-02-18ZHEJIANG ZHIGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593280.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Under outdoor ultraviolet light irradiation, the titanium oxide in the product glue produces free radicals due to photocatalysis, causing yellowing and aging of the resin monomer material.

Method used

Inorganic composite nanoparticles containing titanium oxide are combined with photocuring resin monomers, and UV absorbers and antioxidants are added to form high-refractive index nanoimprinting glue that is resistant to ultraviolet aging.

Benefits of technology

The glue slows down the yellowing and aging speed of the resin monomer material under outdoor ultraviolet light, maintains a high refractive index, and does not affect the preparation of the diffraction light waveguide during the cross-linking curing reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126138790000211
    Figure BDA0005126138790000211
Patent Text Reader

Abstract

The invention provides nano-imprinting glue with ultraviolet aging resistance and high refractive index and a preparation method of the nano-imprinting glue, and the glue comprises the following components in percentage by mass: 45-95% of inorganic composite nanoparticles containing titanium oxide, 1-45% of a light-cured resin monomer, 0.5-15% of a photoinitiator, 0.05-15% of a UV absorbent and 0.05-10% of a leveling aid. The inorganic composite nanoparticles containing titanium oxide are matched with the light-cured resin monomer, so that on one hand, the glue has high refractive index, and on the other hand, the content of titanium oxide in the glue is reduced, thereby reducing the number of free radicals generated by titanium oxide in the glue under the photocatalysis of outdoor ultraviolet light, and improving the light-cured property of the glue. Therefore, the yellowing and aging speed of a resin monomer material in the glue is slowed down. The UV absorbent of the components is further matched with the inorganic composite nanoparticles containing the titanium oxide, and the UV absorbent absorbs outdoor ultraviolet rays irradiating the titanium oxide in the glue, so that free radicals, which cause yellowing and aging of resin monomers, of the titanium oxide are prevented from being generated due to ultraviolet irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diffraction optical waveguide preparation, and in particular relates to a high-refractive-index nanoimprint glue resistant to ultraviolet aging and a preparation method thereof. Background Art

[0002] The existing method for preparing diffractive optical waveguides is generally:

[0003] 1. Prepare an imprint master with a preset grating structure.

[0004] 2. The grating structure of the imprint master is transferred to the soft film through the nanoimprint process to obtain the inverse structure of the grating structure on the soft film.

[0005] Specifically, the embossing glue is evenly spin-coated on the embossing master, the soft film substrate is bonded to the embossing master, pressure is applied to fill the embossing glue into the grating structure of the embossing master, and the inverse structure of the grating structure is obtained on the embossing glue. The embossing glue with the inverse structure of the grating structure is transferred to the soft film substrate by ultraviolet light curing and demolding, so as to obtain a soft film with the inverse structure of the grating structure.

[0006] 3. The inverse structure of the grating structure on the soft film is transferred to the glass wafer through the nanoimprint process to obtain a glass wafer with a grating structure, thereby obtaining a diffraction optical waveguide.

[0007] Specifically, a tackifier and a product glue are spin-coated on a glass wafer in sequence, a soft film with a grating structure inverse structure is bonded to the product glue on the glass wafer, pressure is applied to allow the product glue to fill the grating structure inverse structure of the soft film, a grating structure is obtained on the product glue, ultraviolet light is used for curing and demolding, the soft film with a grating structure inverse structure is separated from the product glue with a grating structure, a glass wafer with a grating structure is obtained, and thus a diffraction optical waveguide is obtained.

[0008] The field of view angle of the diffraction optical waveguide is determined by the refractive index of the material. Under the same design logic, the higher the refractive index of the material, the larger the field of view angle will be.

[0009] At present, the diffraction waveguides that realize full-color functions generally require the refractive index of the product glue to be 1.8 or even 1.9. In order to achieve such a high refractive index, the product glue components need to be realized through the combination of titanium oxide nanoparticles and resin monomer materials. Because titanium oxide has extremely strong photocatalytic activity, and the nano-scale particle morphology will greatly increase the specific surface area of ​​titanium oxide, further amplifying the photocatalytic activity of titanium oxide, the diffraction waveguide is exposed to outdoor ultraviolet light (wavelength of about 340nm) for a long time, and the titanium oxide in the product glue will produce free radicals under the photocatalysis of ultraviolet light. The generated free radicals will cause yellowing and aging of the resin monomer material in the glue. Summary of the invention

[0010] In order to overcome the defects of the prior art, the present invention provides a high-refractive-index nanoimprint glue resistant to ultraviolet aging and a preparation method thereof.

[0011] The present invention is achieved through the following technical solutions:

[0012] The present invention provides a high-refractive-index nanoimprint glue resistant to ultraviolet aging, which comprises the following components by mass percentage:

[0013] Inorganic composite nanoparticles containing titanium oxide 45-95%;

[0014] Photocurable resin monomer 1-45%;

[0015] Photoinitiator 0.5-15%;

[0016] UV absorber 0.05-15%;

[0017] Leveling agent 0.05-10%.

[0018] Furthermore, the following components are included by mass percentage:

[0019] Inorganic composite nanoparticles containing titanium oxide 50-90%;

[0020] Photocurable resin monomer 1-40%;

[0021] Photoinitiator 0.5-10%;

[0022] UV absorber 0.05-10%;

[0023] Leveling agent 0.05-5%.

[0024] Furthermore, the following components are included by mass percentage:

[0025] Inorganic composite nanoparticles containing titanium oxide 55-85%;

[0026] Photocurable resin monomer 5-35%;

[0027] Photoinitiator 1-5%;

[0028] UV absorber 0.05-5%;

[0029] Leveling agent 0.05-2%.

[0030] Furthermore, the UV absorber is a hydroxyphenyl triazine UV absorber, such as the UV absorbers produced by BASF AG, such as Tinuvin 479 and Tinuvin 405.

[0031] Furthermore, the inorganic composite nanoparticles containing titanium oxide preferably have a refractive index of 2.0 or more, and the inorganic composite nanoparticles containing titanium oxide are preferably composite nanoparticles of tin oxide and titanium oxide. The composite nanoparticles of tin oxide and titanium oxide can be obtained from a dispersion of composite nanoparticles of tin oxide and titanium oxide, and the dispersion of composite nanoparticles of tin oxide and titanium oxide can be produced by JGC Catalysts & Chemicals Co., Ltd., and the product model is TR502 (composite nanoparticles of tin oxide and titanium oxide content 20%).

[0032] Furthermore, by weight percentage, it also includes:

[0033] Antioxidants 0.1-10%.

[0034] Preferably, the antioxidant is a composite antioxidant;

[0035] The composite antioxidants include hindered amine antioxidants and hindered phenol antioxidants;

[0036] Calculated by mass percentage, the hindered amine antioxidant is 0.05-5%, and the hindered phenol antioxidant is 0.05-5%.

[0037] For example, the hindered amine antioxidant may be Tinuvin 292, UV123, etc. produced by BASF SE. The hindered phenol antioxidant may be Irganox 1076, Irganox 3114, etc. produced by BASF SE.

[0038] Furthermore, the photocurable resin monomer is a multifunctional photocurable resin monomer. The multifunctional photocurable resin monomer is a multifunctional acrylate monomer that does not contain a benzene ring or a naphthalene ring. For example, 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), trimethylolpropane triacrylate (TMPTA), dipentaerythritol hexaacrylate (DPHA), etc.

[0039] Furthermore, the photoinitiator can be selected from photoinitiators that can quickly initiate cross-linking and curing reactions in the diffraction optical waveguide nanoimprint ultraviolet irradiation band, such as 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylacetophenone, α,α-dimethoxy-α-phenylacetophenone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone.

[0040] For example, the leveling agent is preferably one of BYK310 leveling agent, BYK378 leveling agent, and BYK354 leveling agent produced by BYK Chemical.

[0041] The present invention also provides a method for preparing the above-mentioned high-refractive-index nanoimprint glue resistant to ultraviolet aging, comprising the following steps:

[0042] Weigh the inorganic composite nanoparticles containing titanium oxide, the photocurable resin monomer, the photoinitiator, the UV absorber and the leveling aid according to the mass percentage;

[0043] The photocurable resin monomer, the photoinitiator, the UV absorber and the leveling agent are stirred and mixed evenly, and then the inorganic composite nanoparticles containing titanium oxide are added and stirred and mixed evenly to obtain a high refractive index nanoimprint glue resistant to ultraviolet aging.

[0044] Furthermore, it also includes:

[0045] Weigh 0.1-10% antioxidant by mass percentage;

[0046] The photocurable resin monomer, the photoinitiator, the UV absorber, the leveling agent and the antioxidant are stirred and mixed evenly, and then the inorganic composite nanoparticles containing titanium oxide are added and stirred and mixed evenly to obtain a high refractive index nanoimprint glue resistant to ultraviolet aging.

[0047] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0048] The high-refractive-index nanoimprint glue resistant to ultraviolet aging provided by the present invention adopts the inorganic composite nanoparticles containing titanium oxide as the component to be matched with a photocurable resin monomer, which ensures that the glue has a high refractive index on the one hand, and reduces the content of titanium oxide in the glue on the other hand, thereby weakening the number of free radicals generated by the titanium oxide in the glue under the photocatalysis of outdoor ultraviolet light, thereby slowing down the yellowing and aging speed of the resin monomer material in the glue. The UV absorber of the component is further matched with the inorganic composite nanoparticles containing titanium oxide, and the UV absorber can absorb outdoor ultraviolet light irradiating the titanium oxide in the glue, thereby preventing the titanium oxide from generating free radicals that cause yellowing and aging of the resin monomer due to ultraviolet light irradiation at the root.

[0049] The UV absorber of the high refractive index nanoimprint glue resistant to ultraviolet aging provided by the present invention is preferably a hydroxyphenyl triazine type UV absorber. The hydroxyphenyl triazine type UV absorber has a high absorptivity to outdoor ultraviolet rays (wavelength of about 340nm) and a high transmittance to the diffraction light waveguide nanoimprint ultraviolet light irradiation band (wavelength of about 365nm), so that the UV absorber in the glue absorbs outdoor ultraviolet rays irradiating the titanium oxide in the glue to prevent the titanium oxide from generating free radicals that cause yellowing and aging of the resin monomer due to ultraviolet light irradiation at the root, and the UV absorber in the glue will not effectively absorb the ultraviolet light band in the ultraviolet light curing process in the diffraction light waveguide nanoimprint process, so as not to have an adverse effect on the ultraviolet light curing process of the glue in the diffraction light waveguide nanoimprint process.

[0050] The high-refractive-index nanoimprint glue resistant to ultraviolet aging provided by the present invention is further added with 0.1-10% of an antioxidant by mass percentage, which is matched with the inorganic composite nanoparticles containing titanium oxide and the UV absorber of the above components. The antioxidant can react with free radicals generated by the titanium oxide in the glue under the photocatalysis of outdoor ultraviolet light, thereby weakening or even eliminating the yellowing and aging phenomenon of the resin monomer material in the glue caused by the free radicals generated by the titanium oxide in the glue under the photocatalysis of outdoor ultraviolet light.

[0051] And further preferably, the antioxidant adopts a composite antioxidant including a hindered amine antioxidant and a hindered phenol antioxidant, and by mass percentage, the hindered amine antioxidant is 0.05-5%, and the hindered phenol antioxidant is 0.05-5%. By adjusting the ratio of the hindered amine antioxidant with lower reaction activity and the hindered phenol antioxidant with higher reaction activity, the action life of the antioxidant is improved, and the hindered phenol antioxidant with too high reaction activity is avoided to react with the free radicals generated by the photoinitiator under ultraviolet light to promote the ultraviolet curing reaction, thereby affecting the cross-linking and curing reaction of the glue, and avoiding the relatively low reaction activity of the hindered amine antioxidant. The reaction fails to react with the free radicals generated by the titanium oxide in the glue under the photocatalysis of outdoor ultraviolet light in time, thereby failing to inhibit the yellowing and aging of the resin monomer material in the glue caused by the free radicals generated by the titanium oxide in the glue under the photocatalysis of outdoor ultraviolet light.

[0052] The UV absorber and antioxidant added to the high-refractive-index nanoimprint glue resistant to ultraviolet aging provided by the present invention do not participate in the cross-linking and curing reaction under ultraviolet light irradiation in the diffraction optical waveguide nanoimprinting process. Therefore, preferably, the photocurable resin monomer of the present invention adopts a multifunctional photocurable resin monomer, thereby enhancing the cross-linking density of the glue and improving the strength of the glue.

[0053] The high-refractive-index nanoimprint glue resistant to ultraviolet aging provided by the present invention has a photoinitiator that can quickly initiate a crosslinking and curing reaction in the ultraviolet irradiation band of the diffraction light waveguide nanoimprint, thereby preventing the UV absorber from absorbing the ultraviolet irradiation band of the diffraction light waveguide nanoimprint and affecting the crosslinking and curing reaction of the glue, and preventing the antioxidant from reacting with the photoinitiator under ultraviolet light to produce free radicals that promote the ultraviolet curing reaction and affect the crosslinking and curing reaction of the glue. DETAILED DESCRIPTION

[0054] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] In this article, the terms "first", "second" and other similar words are not intended to imply any order, quantity and importance, but are only used to distinguish different elements. In this article, the terms "one", "an" and other similar words are not intended to indicate that there is only one of the things described, but rather indicate that the relevant description is only for one of the things described, and the things described may have one or more. In this article, the terms "comprise", "include" and other similar words are intended to indicate logical mutual relationships, and cannot be regarded as indicating spatial structural relationships. For example, "A includes B" is intended to indicate that B belongs to A logically, but does not indicate that B is located inside A spatially. In addition, the meanings of the terms "comprise", "include" and other similar words should be regarded as open, rather than closed. For example, "A includes B" is intended to indicate that B belongs to A, but B does not necessarily constitute the whole of A, and A may also include other elements such as C, D, and E.

[0056] In this document, the terms "embodiment", "present embodiment", "preferred embodiment", and "one embodiment" do not mean that the relevant description is only applicable to a specific embodiment, but rather that the description may also be applicable to one or more other embodiments. Those skilled in the art should understand that in this document, any description of a certain embodiment can be replaced, combined, or combined in other ways with the relevant description in one or more other embodiments, and the new embodiment generated by the replacement, combination, or combination in other ways is easily conceivable by those skilled in the art and falls within the scope of protection of the present invention.

[0057] In the description herein, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0058] Example 1

[0059] The ultraviolet aging resistant high refractive index nanoimprint glue provided in this embodiment is composed of the following components in parts by mass:

[0060] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0061] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g;

[0062] Hindered amine antioxidant (produced by BASF, product model: Tinuvin 292): 0.5 g;

[0063] Hindered phenol antioxidant (produced by BASF AG, product model: Irganox 1076): 1.5 g;

[0064] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0065] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0066] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0067] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0068] The method for preparing the ultraviolet aging resistant high refractive index nanoimprint glue of this embodiment comprises the following steps:

[0069] According to the above masses, trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0070] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm for 3 minutes in a centrifugal mixer to obtain a high refractive index nanoimprint glue resistant to UV aging.

[0071] Example 2

[0072] The ultraviolet aging resistant high refractive index nanoimprint glue provided in this embodiment is composed of the following components in parts by mass:

[0073] Trimethylolpropane triacrylate (TMPTA): 27.5 g;

[0074] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g;

[0075] Hindered amine antioxidant (produced by BASF, product model: Tinuvin 292): 0.5 g;

[0076] Hindered phenol antioxidant (produced by BASF AG, product model: Irganox 1076): 1.5 g;

[0077] 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylacetophenone: 2 g;

[0078] α,α-dimethoxy-α-phenylacetophenone: 2g;

[0079] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0080] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 320 g.

[0081] The method for preparing the ultraviolet aging resistant high refractive index nanoimprint glue of this embodiment comprises the following steps:

[0082] According to the above masses, trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox1076), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylacetophenone, α,α-dimethoxy-α-phenylacetophenone, leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0083] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylacetophenone, α,α-dimethoxy-α-phenylacetophenone, and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm for 3 minutes in a centrifugal mixer to obtain a high refractive index nanoimprint glue resistant to UV aging.

[0084] Comparative Example 1

[0085] The nanoimprint glue of this comparative example is composed of the following components in parts by mass:

[0086] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0087] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0088] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0089] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0090] Titanium oxide nanoparticle dispersion (produced by Daisei Chemical Industry Co., Ltd., product model: TTP-1132, titanium oxide nanoparticle content 40%): 200 g.

[0091] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0092] According to the above mass, trimethylolpropane triacrylate (TMPTA), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and titanium oxide nanoparticle dispersion (produced by Daisei Chemical Co., Ltd., product model: TTP-1132, titanium oxide nanoparticle content 40%) were weighed respectively.

[0093] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of titanium oxide nanoparticle dispersion (produced by Daisei Chemical Co., Ltd., product model: TTP-1132, titanium oxide nanoparticle content 40%) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0094] Comparative Example 2

[0095] The nanoimprint glue provided in this comparative example is composed of the following components in parts by mass:

[0096] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0097] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0098] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0099] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0100] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0101] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0102] According to the above masses, trimethylolpropane triacrylate (TMPTA), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), a leveling agent (produced by BYK Chemical, product model: BYK310) and a composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0103] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0104] Comparative Example 3

[0105] The nanoimprint glue provided in this comparative example is composed of the following components in parts by mass:

[0106] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0107] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g; 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2g;

[0108] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0109] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0110] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0111] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0112] According to the above masses, trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) were weighed respectively.

[0113] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0114] Comparative Example 4

[0115] The nanoimprint glue of this comparative example is composed of the following components in parts by mass:

[0116] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0117] Benzotriazole UV absorber (produced by BASF AG, product model: Tinuvin 384-2): 2g;

[0118] Hindered amine antioxidant (produced by BASF, product model: Tinuvin 292): 0.5 g;

[0119] Hindered phenol antioxidant (produced by BASF AG, product model: Irganox 1076): 1.5 g;

[0120] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0121] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0122] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0123] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0124] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0125] According to the above masses, trimethylolpropane triacrylate (TMPTA), benzotriazole UV absorber (produced by BASF, product model: Tinuvin 384-2), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0126] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), benzotriazole UV absorber (produced by BASF, product model: Tinuvin 384-2), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0127] Comparative Example 5

[0128] The nanoimprint glue of this comparative example is composed of the following components in parts by mass:

[0129] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0130] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g;

[0131] Hindered amine antioxidant (produced by BASF AG, product model: Tinuvin 292): 2g;

[0132] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0133] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0134] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0135] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0136] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0137] According to the above masses, trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0138] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0139] Comparative Example 6

[0140] The nanoimprint glue of this comparative example is composed of the following components in parts by mass:

[0141] Acryloylmorpholine (ACMO): 11.5 g;

[0142] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g;

[0143] Hindered amine antioxidant (produced by BASF, product model: Tinuvin 292): 0.5 g;

[0144] Hindered phenol antioxidant (produced by BASF AG, product model: Irganox 1076): 1.5 g;

[0145] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0146] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0147] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0148] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0149] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0150] According to the above masses, acryloyl morpholine (ACMO), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0151] The above-mentioned mass of acryloyl morpholine (ACMO), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0152] Comparative Example 7

[0153] The nanoimprint glue of this comparative example is composed of the following components in parts by mass:

[0154] Trimethylolpropane triacrylate (TMPTA): 11.5 g;

[0155] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g;

[0156] Hindered amine antioxidant (produced by BASF, product model: Tinuvin 292): 0.5 g;

[0157] Hindered phenol antioxidant (produced by BASF AG, product model: Irganox 1076): 1.5 g;

[0158] Methyl benzoylformate (MBF): 4g;

[0159] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0160] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0161] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0162] According to the above masses, trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox1076), methyl benzoylformate (MBF), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0163] The above-mentioned mass of trimethylolpropane triacrylate (TMPTA), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), methyl benzoylformate (MBF), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of tin oxide and titanium oxide composite nanoparticle dispersion (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0164] Comparative Example 8

[0165] The nanoimprint glue provided in this comparative example is composed of the following components in parts by mass:

[0166] 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene (BPEF): 11.5 g;

[0167] Hydroxyphenyl triazine UV absorber (produced by BASF AG, product model: Tinuvin 479): 2g;

[0168] Hindered amine antioxidant (produced by BASF, product model: Tinuvin 292): 0.5 g;

[0169] Hindered phenol antioxidant (produced by BASF AG, product model: Irganox 1076): 1.5 g;

[0170] 2-Hydroxy-2-methyl-1-phenyl-1-propanone (1173): 2 g;

[0171] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO): 2g;

[0172] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0173] Composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502): 400 g.

[0174] The preparation method of the nanoimprint glue of this comparative example comprises the following steps:

[0175] According to the above masses, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene (BPEF), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), leveling agent (produced by BYK Chemical, product model: BYK310) and composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals, Ltd., product model: TR502) were weighed respectively.

[0176] The above-mentioned mass of 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene (BPEF), hydroxyphenyl triazine UV absorber (produced by BASF, product model: Tinuvin 479), hindered amine antioxidant (produced by BASF, product model: Tinuvin 292), hindered phenol antioxidant (produced by BASF, product model: Irganox 1076), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of composite nanoparticle dispersion of tin oxide and titanium oxide (produced by JGC Catalysts & Chemicals Co., Ltd., product model: TR502) is added, and the mixture is stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint glue.

[0177] The nanoimprint process of applying the nanoimprint glue of the above-mentioned Examples 1-2 and Comparative Examples 1-8 to the diffractive optical waveguide is as follows:

[0178] 1. Prepare an imprint master with a preset grating structure.

[0179] 2. Transfer the grating structure of the imprint master to the soft film through the nanoimprint process to obtain the inverse structure of the grating structure on the soft film;

[0180] Specifically,

[0181] The imprint glue is evenly spin-coated on the imprint master, the soft film substrate is bonded to the imprint master, and pressure is applied to fill the imprint glue into the grating structure of the imprint master, and the inverse structure of the grating structure is obtained on the imprint glue. The imprint glue with the inverse structure of the grating structure is transferred to the soft film substrate by ultraviolet light curing and demolding, and a soft film with the inverse structure of the grating structure is obtained.

[0182] 3. The inverse structure of the grating structure on the soft film is transferred to the waveguide substrate through a nanoimprint process to obtain a waveguide substrate with a grating structure, thereby obtaining a diffraction optical waveguide.

[0183] Specifically,

[0184] A glass wafer (i.e., a waveguide substrate) with a surface subjected to adhesion enhancement treatment is placed on a glue spreader, and the nanoimprint glues of the above-mentioned embodiments 1-2 and comparative examples 1-8 are respectively added and spin-coated to obtain a uniform glue film layer with a nanometer-level thickness; a soft film with a grating structure inverse structure is pressed onto the glue film layer to obtain a grating structure on the glue film layer; then, an ultraviolet light source is irradiated to solidify the glue film layer with the grating structure, and then the soft film with the grating structure inverse structure is separated from the glue film layer with the grating structure, and demolding is completed to obtain a diffraction optical waveguide product with a grating structure.

[0185] The performance tests of the nanoimprint glues of the above-mentioned Examples 1-2 and Comparative Examples 1-8 in the diffraction optical waveguide nanoimprint process are as follows:

[0186] Refractive index test: Use an ellipsometer to test the refractive index of the adhesive layer of the diffraction optical waveguide product to obtain the refractive index of the adhesive layer at a wavelength of 532nm (it should be noted that the 532nm wavelength is only an example, and other wavelengths can also be used).

[0187] Thermal weight loss experiment: Place the diffraction optical waveguide product in a 150°C oven and bake for 30 minutes, and test the weight loss of the colloid after baking.

[0188] Ultrasonic cleaning: Place the diffraction optical waveguide in an ultrasonic cleaning machine (cleaning agent is clean water, ultrasonic frequency is 430 Hz) for 30 minutes, then take it out and dry it, and observe whether the adhesive layer is damaged.

[0189] UV aging experiment: The diffraction optical waveguide was irradiated with UV light (340 nm wavelength) for 1 hour and 42 minutes, and then sprayed with 65°C water for 18 minutes as one cycle, and continued for 120 cycles.

[0190] The diffraction optical waveguide product is tested by an ultraviolet spectrophotometer to obtain the yellow-blue coordinate value (b value) in the color space coordinates. The b value can reflect the yellowing and aging degree of the adhesive layer. The smaller the b value tested after the ultraviolet aging experiment, the better the yellowing and aging resistance of the adhesive layer.

[0191] The test results are shown in Table 1:

[0192] Table 1

[0193]

[0194] Note: “ / ” in the table means that this test was not performed.

[0195] It can be seen from the test results of Examples 1-2 in the above table that the nanoimprint glue provided by the present invention can meet the refractive index of 1.8 or even above 1.9. At the same time, it can be seen from the b value that the nanoimprint glue has strong yellowing resistance and aging resistance under the irradiation of ultraviolet light in the 340 band (i.e., outdoor ultraviolet light band).

[0196] By comparing the test results of Comparative Example 1 and Comparative Example 2, it can be seen that the use of inorganic composite nanoparticles containing titanium oxide makes the glue have better yellowing resistance and aging resistance than the use of conventional titanium oxide nanoparticle system.

[0197] By comparing the test results of Comparative Example 2 and Comparative Example 3, it can be seen that the UV absorber is further combined with the inorganic composite nanoparticles containing titanium oxide, so that the yellowing resistance and aging resistance of the glue are better.

[0198] By comparing the test results of Comparative Example 3 and Example 1, it can be seen that the antioxidant is combined with the inorganic composite nanoparticles containing titanium oxide and the UV absorber to further improve the yellowing resistance and aging resistance of the glue.

[0199] By comparing the test results of Example 1 and Comparative Example 4, it can be seen that the use of hydroxyphenyl triazine UV absorbers has less influence on the UV curing process of the glue in the diffraction optical waveguide nanoimprinting process than the use of benzotriazole UV absorbers.

[0200] By comparing the test results of Example 1 and Comparative Example 5, it can be seen that the antioxidant adopts a composite antioxidant including a hindered amine antioxidant and a hindered phenol antioxidant, and by adjusting the ratio of the hindered amine antioxidant with lower reaction activity and the hindered phenol antioxidant with higher reaction activity, the yellowing resistance and aging resistance of the glue are greatly improved.

[0201] By comparing the test results of Example 1 and Comparative Example 6, it can be seen that when a UV absorber and an antioxidant that do not participate in the cross-linking and curing reaction under ultraviolet light irradiation in the diffraction optical waveguide nanoimprinting process are added to the glue, the use of a multifunctional photocurable resin monomer can enhance the cross-linking density of the glue and improve the strength of the glue.

[0202] By comparing the test results of Example 1 and Comparative Example 7, it can be seen that the photoinitiator selected to quickly initiate a cross-linking curing reaction in the diffractive optical waveguide nanoimprinting ultraviolet irradiation band can improve the ultraviolet curing effect of the glue in the diffractive optical waveguide nanoimprinting process.

[0203] By comparing the test results of Example 1 and Comparative Example 8, it can be seen that the acrylate monomer containing a benzene ring will make the glue have poor yellowing resistance and aging resistance.

[0204] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.

Claims

1. A high refractive index nanoimprint glue resistant to ultraviolet aging, characterized in that: Calculated by mass percentage, it includes the following components: Inorganic composite nanoparticles containing titanium oxide 45-95%; Photocurable resin monomer 1-45%; Photoinitiator 0.5-15%; UV absorber 0.05-15%; Leveling agent 0.05-10%.

2. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: Inorganic composite nanoparticles containing titanium oxide 50-90%; Photocurable resin monomer 1-40%; Photoinitiator 0.5-10%; UV absorber 0.05-10%; Leveling agent 0.05-5%.

3. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: Inorganic composite nanoparticles containing titanium oxide 55-85%; Photocurable resin monomer 5-35%; Photoinitiator 1-5%; UV absorber 0.05-5%; Leveling agent 0.05-2%.

4. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to any one of claims 1 to 3, characterized in that: The UV absorber is a hydroxyphenyl triazine UV absorber.

5. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to any one of claims 1 to 3, characterized in that: The inorganic composite nanoparticles containing titanium oxide are composite nanoparticles of tin oxide and titanium oxide.

6. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to claim 1, characterized in that: In terms of mass percentage, it also includes: Antioxidants 0.1-10%.

7. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to claim 6, characterized in that: The antioxidant is a composite antioxidant; The composite antioxidant includes hindered amine antioxidants and hindered phenol antioxidants; Calculated by mass percentage, the hindered amine antioxidant is 0.05-5%, and the hindered phenol antioxidant is 0.05-5%.

8. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to any one of claims 1 to 7, characterized in that: The photocurable resin monomer is a multifunctional photocurable resin monomer.

9. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to claim 8, characterized in that: The multifunctional photocurable resin monomer is a multifunctional acrylate monomer that does not contain a benzene ring or a naphthalene ring.

10. The high-refractive-index nanoimprint glue resistant to ultraviolet aging according to any one of claims 1 to 7, characterized in that: The photoinitiator is a photoinitiator that can quickly initiate a cross-linking curing reaction in the diffraction light waveguide nanoimprint ultraviolet irradiation band.

11. The method for preparing the ultraviolet aging resistant high refractive index nanoimprint glue according to any one of claims 1 to 5, characterized in that: The steps include: Weigh the inorganic composite nanoparticles containing titanium oxide, the photocurable resin monomer, the photoinitiator, the UV absorber and the leveling aid according to the mass percentage; The photocurable resin monomer, the photoinitiator, the UV absorber and the leveling agent are stirred and mixed evenly, and then the inorganic composite nanoparticles containing titanium oxide are added and stirred and mixed evenly to obtain a high refractive index nanoimprint glue resistant to ultraviolet aging.

12. The method for preparing the ultraviolet aging resistant high refractive index nanoimprint glue according to claim 11, characterized in that: Also includes: Weigh 0.1-10% antioxidant by mass percentage; The photocurable resin monomer, the photoinitiator, the UV absorber, the leveling agent and the antioxidant are stirred and mixed evenly, and then the inorganic composite nanoparticles containing titanium oxide are added and stirred and mixed evenly to obtain a high refractive index nanoimprint glue resistant to ultraviolet aging.